Aplicação de opções reais em projetos de automação: um estudo de caso na indústria de cerveja - Bellan, Stener (2015)
Industrial automation projects are evaluated financially through the widely used methods of Net Present Value (NPV) and Internal Rate of Return (IRR). Recent studies show a tendency to use other methods of performing this assessment. This paper explores the alternative method of Real Options for evaluation of these projects seeking to get closer to the real world, considering greater uncertainty and flexibility than the NPV. Initially it will be shown a literature review focusing on the binomial method in Real Options. The proposed methodology is a case study of a project in the beer market in Brazil, using as source a large multinational company supplying this project. Later a financial analysis will be done primarily using only the NPV and later incorporating the binomial method of Real Options, resulting in the extended VPL. The goal is to price the flexibility of Real Options present in the design of the supply contract under consideration that are not normally considered. This is intended to verify that the binomial method of real options makes real difference in the project under study.